Путешествие Нильса с дикими гусями - Лагерлеф Сельма (Книги - мои друзья, 2018)
Экземпляры: СБ (20190219) / Инвентарный номер: 57142 / Цена: 100.00 / Сис.шифр: И(шве)мл / Авт.знак: Л 14 / ГРНТИ: 17.82.93 / ББК: 84(4Шве)